WORK BASED LEARNING ONE: DEVELOPING ADVANCED CLINICAL WORK BASED LEARNING - Singh, Bhim (International Journal of Psychosocial Rehabilitation, 2021)
Advancement in clinical practice is measured by a person's master's degree in clinical practice and their ability to use their expert clinical knowledge and abilities in clinical practice. "They are able to operate independently in terms of evaluating patients, diagnosing them, and treating them," the article states. By 2020, there will be a million more people over 65, 7,000 people over 100, and two-thirds of new-borns born today will live to be 100. There is a demand for ACPs in the healthcare globe market. Having a long and illustrious history, nurses have an important role to play in serving the different requirements of the general population.